2016
DOI: 10.1158/0008-5472.can-16-1479
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Mechanism of Action Confounds Early Assessment of Treatment Response by 3′-Deoxy-3′-[18F]Fluorothymidine in Preclinical Models of Lung Cancer

Abstract: 3′-Deoxy-3′-[18F]fluorothymidine positron emission tomography ([18F]FLT-PET) and diffusion-weighted MRI (DW-MRI) are promising approaches to monitor tumor therapy response. Here, we employed these two imaging modalities to evaluate the response of lung carcinoma xenografts in mice after gemcitabine therapy. Caliper measurements revealed that H1975 xenografts responded to gemcitabine treatment, whereas A549 growth was not affected. In both tumor models, uptake of [18F]FLT was significantly reduced 6 hours after… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…Early changes of [ 18 F] FLT uptake in tumors reflected mechanisms such as competing gemcitabine uptake or gemcitabine-induced thymidylate synthase inhibition and only reflected growth inhibitory effects at a later time point [36]. Another study reported early response evaluation using NaF PET in osteosarcoma [37].…”
Section: Early Response Assessments and Imaging Biomarkersmentioning
confidence: 99%
“…Early changes of [ 18 F] FLT uptake in tumors reflected mechanisms such as competing gemcitabine uptake or gemcitabine-induced thymidylate synthase inhibition and only reflected growth inhibitory effects at a later time point [36]. Another study reported early response evaluation using NaF PET in osteosarcoma [37].…”
Section: Early Response Assessments and Imaging Biomarkersmentioning
confidence: 99%
“…Preclinical models have explored changes on FLT uptake following gemcitabine administration and confirmed direct competition of gemcitabine with the radiotracer for cellular uptake; correlation with TK1 expression has also been confirmed [23]. In this study, the aim was to assess the feasibility of imaging proliferation using FLT-PET in patients with advanced PDAC.…”
Section: Introductionmentioning
confidence: 80%
“…However, the absence of tumoural FLT flare with gemcitabine unlike fluoropyrimdines, in preclinical models has been attributed to the competition in tumoural uptake between FLT and gemcitabine, both of which use the same nucleoside transporter, hENT1. It is difficult to delineate if the decreased uptake in tumour and normal tissues in this subject is a true representation of decreased proliferative activity, or as a result of competition between gemcitabine and FLT for transport in to tissue [23,37]. No relationship between the imaging and pathologic parameters were identified.…”
Section: Discussionmentioning
confidence: 97%
“…8-to 12-week-old female NMRI nude mice (Janvier Labs) were used for the experiments. A total of 47 mice were employed in this study, which were initially used to monitor the response of subcutaneous lung cancer xenografts to chemotherapy (10). Mice were treated with intraperitoneal injections of 100 mg/kg gemcitabine in 100 mL 0.9% NaCl or 0.9% NaCl vehicle control on days 0 and 3.…”
Section: Animal Modelmentioning
confidence: 99%